2011
DOI: 10.1128/mcb.05744-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Cancer-Associated Mutations in the Aα Subunit of Protein Phosphatase 2A Increase Lung Cancer Incidence in Aα Knock-In and Knockout Mice

Abstract: Strong evidence has indicated that protein phosphatase 2A (PP2A) is a tumor suppressor, but a mouse model for testing the tumor suppressor activity was missing. The most abundant forms of trimeric PP2A holoenzyme consist of the scaffolding A␣ subunit, one of several regulatory B subunits, and the catalytic C␣ subunit. A␣ mutations were discovered in a variety of human carcinomas. All carcinoma-associated mutant A␣ subunits are defective in binding the B or B and C subunits. Here we describe two knock-in mice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 86 publications
6
99
0
Order By: Relevance
“…SV40 small tumor antigen and polyomavirus small and middle tumor antigens each associate with PP2A and displace B subunits, and this activity is essential for their cell transformation function (18). Cancer-associated mutations in the PP2A A subunit render the A subunit defective for binding B or C subunits, and expression of these mutant PP2A proteins in mice increases tumor formation, providing additional evidence that dysregulation of PP2A activity is cancer promoting (87).…”
Section: Discussionmentioning
confidence: 97%
“…SV40 small tumor antigen and polyomavirus small and middle tumor antigens each associate with PP2A and displace B subunits, and this activity is essential for their cell transformation function (18). Cancer-associated mutations in the PP2A A subunit render the A subunit defective for binding B or C subunits, and expression of these mutant PP2A proteins in mice increases tumor formation, providing additional evidence that dysregulation of PP2A activity is cancer promoting (87).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated a link between PP2A and a number of diseases (Janssens et al 2005, Rivera & Losada 2006, Krapf et al 2010, Brestovitsky et al 2011, Ruediger et al 2011. Its catalytic subunit PP2AC plays a critical role in embryonic development and human diseases, such as Alzheimer's disease, cancer, and diabetes (Goedert et al 1995, Zolnierowicz 2000, Kowluru 2005, Eichhorn et al 2009, Liu & Wang 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Within the PPP family, the catalytic subunits of PP2A, PP4 and PP6 are most closely related, and the three proteins form a subfamily called PP2A-like protein phosphatases that account for the majority of cellular serine/ threonine phosphatase activity (Janssens and Goris, 2001;Moorhead et al, 2007). PP2A is involved in regulating chromosome condensation, DNA damage repair, the G2/M transition and sister chromatid cohesion (Ruediger et al, 2011). We have recently shown that PP2A is essential for female meiosis and fertility because oocyte-specific depletion of PP2A facilitates GVBD, causes elongated MII spindles and precocious separation of sister chromatids, resulting in defective early embryonic development, and thus subfertility .…”
Section: Introductionmentioning
confidence: 99%